Observer error in histological assessment of marrow hypocellularity. Issue 2 (February 1975) - Morley, A; Blake, J
Abstract : Observer error in the assessment of marrow hypocellularity was studied by examining histological sections from 37 mice having normal or reduced marrow cellularity and comparing the estimated cellularity with a previously measured value. For marrows or mild or moderately reduced cellularity the subjective estimate of cellularity was almost valueless both in terms of accuracy and reproducibility. Only severely hypocellular marrows, having a cellularity of less than 17% of normal, could be recognized as being abnormal with some degree of accuracy and reproducibility.